Shooting shots: Estimating alcoholic drink sizes in real life using event‐level reports and annotations of close‐up pictures. (17th November 2020) - Labhart, Florian; Phan, Thanh‐Trung; Gatica‐Perez, Daniel; Kuntsche, Emmanuel
Abstract: Introduction and Aims: Drinks consumed in real life are diverse, in terms of beverage type, container size and alcohol by volume. To date, most ecological momentary assessment studies have assessed drinking amounts with 'standard' drinks, although their event‐level design allows for more advanced assessment schemes. The purpose of this empirical study is to compare participants' estimates of alcoholic drink characteristics, assessed using drink‐specific questions, with estimates generated by annotators based on pictures of the same drinks. Design and Methods: On weekend nights, 186 young adults took 1484 close‐up pictures of their drinks using a custom‐built smartphone application. Participants reported the beverage type, drink size and alcohol by volume. Annotators described the beverage type, container size and filling level. Correspondence between participants' and annotators' estimates was explored using descriptive statistics, difference tests and correlations. Results: Annotators were unable to precisely identify the beverage types in most pictures of liqueurs, spirits and mixed drinks. Participants' drink size estimates converged with annotators' estimates of the container size for beer (41 cl corresponding to 16 g of pure alcohol) and mixed drinks (28 cl/35 g), and of the content size for wine (10 cl/9 g). However, annotators estimated larger sizes for liqueur/fortified wine (12 cl/14 g vs. 7 cl/9 g) and spirits (8 cl/26 g vs. 4 cl/10 g) than participants. Discussion and Conclusions: Annotations of pictures should be considered as a complement to participants' reports rather than a substitute. Except for wine, real‐life drinks vary largely and often exceed 10 g 'standard' drinks.